Dengue risk prediction in illegal dumpsite of housing area by using geospatial analysis - Zen, Irina Safitri (2019)
Malaysia suffered from several dengue epidemics with a highly contagious health threat in the last few decades. Analyses of the incidence number of dengue cases and the illegal dumpsite by using the Geographical Information System, GIS, standard deviational ellipse, SDE, produces a scientific-based evidence of dengue map for the urbanized area of Iskandar Puteri, Johor State, Malaysia. A high incidence of dengue cases in the illegal dumpsite area was recognized in radius 200 to 1000 meter with the trend towards the east and west of the city with standard distance (STD) value 0.03. It was identified as a high spot area. It was noteworthy that illegal dumpsite has potential to be a predictive tool for dengue risk to prevent the outbreak. Furthermore, the study recognized the sites i.e. pedestrian walkway, roadside, abundant land and riverside as a spotted illegal dumpsite. Nevertheless, an increment about 40 percent out of the total cost to manage illegal dumpsite from 2011 to 2016 is showing the urgency in tackling this problem comprehensively. Close monitoring system on the sub- contractor of waste disposal collection works and having concentrated effort by involving the relevant government agencies are among crucial issues need to be tackled to solve dengue problem related with illegal dumpsite.